2022
DOI: 10.1123/ijspp.2021-0514
|View full text |Cite
|
Sign up to set email alerts
|

Postlockdown Performance in French Swimming Championships

Abstract: Purpose: To measure the proportion of French swimmers that progressed, stagnated, or regressed during the 2020 national championship compared with previous ones. Method: Individual best performances were collected at the French national championships from 2000 to 2020. Yearly proportions of swimmers who improved, stagnated, or regressed in performances were compared with their previous performances. Results: In 2020, the proportion of swimmers with performance regression has significantly increased (33% vs 17%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…This evidence supports our decision to fail to reject the Everybody-Was-Impacted Hypothesis with the forecasted data. These findings are consistent with Miguens et al (2022), which used a panel dataset to compare the probability of improvement or regression in French swimming from 2000-2020. In the 2020 national championships, a higher proportion of distance swimmers and breaststrokers regressed due to lockdowns during the pandemic.…”
Section: Data Collection and Testing Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…This evidence supports our decision to fail to reject the Everybody-Was-Impacted Hypothesis with the forecasted data. These findings are consistent with Miguens et al (2022), which used a panel dataset to compare the probability of improvement or regression in French swimming from 2000-2020. In the 2020 national championships, a higher proportion of distance swimmers and breaststrokers regressed due to lockdowns during the pandemic.…”
Section: Data Collection and Testing Methodssupporting
confidence: 87%
“…It is related to previous research in sports economics that reached conclusions based on data from surveys, like Lee and Park (2010), which studied physical activity and happiness in South Korea. Finally, this study joins Haddad et al (2021) and Miguens et al (2022) in studying how the pandemic affected swimming performances, and previous works such as Harris (2020) and McFall et al (2020), which studied the sport of swimming or elite swimming performance.…”
Section: Introductionmentioning
confidence: 90%
“…Some studies performed in other countries have shown that the pandemic influenced swimming performance in competitive athletes. In particular, a performance regression was registered during the 2020 French national championships, after eight weeks of lockdown without training, mainly among females, long-distance, and breaststroke swimmers [ 26 ]; the analysis of data points from Poland, Spain, Russia, Turkey, and Denmark championships from 2019 to 2020 showed improvements in symmetrical techniques, i.e., breaststroke and butterfly [ 27 ]; a performance analysis carried out on a collegiate USA swimming team between the 2020–2021 and 2019–2020 seasons highlighted significant reductions in swim training volume, with sprinters performing better and long-distance swimmers performing worse at the regional championships [ 20 ]; and a performance time deterioration in the 200, 300, and 400 m was found in Greek swimmers after an 11-week lockdown, while no changes were detected in 4 × 50 m and 50 m tests [ 28 ]. These findings suggest that the pandemic caused significant abstention from swimming and a reduction in training volume, leading to reduced aerobic fitness and impaired technical ability; when adopted, dryland training allowed the athletes to maintain strength and to preserve their sprint ability.…”
Section: Discussionmentioning
confidence: 99%